2018
DOI: 10.1088/1475-7516/2018/04/033
|View full text |Cite
|
Sign up to set email alerts
|

Lensing convergence in galaxy clustering in ΛCDM and beyond

Abstract: We study the impact of neglecting lensing magnification in galaxy clustering analyses for future galaxy surveys, considering the ΛCDM model and two extensions: massive neutrinos and modifications of General Relativity. Our study focuses on the biases on the constraints and on the estimation of the cosmological parameters. We perform a comprehensive investigation of these two effects for the upcoming photometric and spectroscopic galaxy surveys Euclid and SKA for different redshift binning configurations. We al… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 125 publications
2
31
0
Order By: Relevance
“…As expected, standard tomography is very sensitive to lensing effects, because its wider redshift bins acquire a significant contribution from the integrated effect of lensing. On the other hand, the thinner the bin, the less important is lensing (see also Villa et al 2018). Thus, our hybrid approach, with its thin sub-bins, is almost insensitive to it, and we can therefore safely ignore the lensing contribution in the hybrid approach.…”
Section: Bias On Parameter Estimation From Neglecting Lensingmentioning
confidence: 99%
“…As expected, standard tomography is very sensitive to lensing effects, because its wider redshift bins acquire a significant contribution from the integrated effect of lensing. On the other hand, the thinner the bin, the less important is lensing (see also Villa et al 2018). Thus, our hybrid approach, with its thin sub-bins, is almost insensitive to it, and we can therefore safely ignore the lensing contribution in the hybrid approach.…”
Section: Bias On Parameter Estimation From Neglecting Lensingmentioning
confidence: 99%
“…The inclusion of the lensing magnification in cross and auto-correlations of galaxy clustering and cosmic shear has been studied with Fisher analysis (Duncan et al 2013;Villa et al 2018;Thiele et al 2019), where it has already been suggested that the ignorance of the magnification bias may induce a bias in the cosmological parameter estimation. Here, we test this hypothesis by performing a full likelihood mock data analysis.…”
Section: Galaxy Number Counts and Magnification Biasmentioning
confidence: 99%
“…We derive constraints on the directions and amplitudes of anisotropies for both a Euclid-like and SKA2-like survey. The specifications for these surveys are taken from [53] and [54] respectively: the two redshift ranges are z ∈ [0.7, 2.0] for Euclid and z ∈ [0.1, 2.0] for SKA2 and we split them into 14 and 19 bins of thickness ∆z = 0.1 respectively, with L p = 2 Mpc/h. This choice of L p is motivated by the fact that this pixel size gives the best constraints in [25].…”
Section: A Model For Vector Perturbationsmentioning
confidence: 99%